2016
DOI: 10.1111/epi.13312
|View full text |Cite
|
Sign up to set email alerts
|

Postictal immobility and generalized EEG suppression are associated with the severity of respiratory dysfunction

Abstract: Summary Objective The pathophysiology of sudden unexpected death in epilepsy (SUDEP) remains undetermined. Seizures are accompanied by respiratory dysfunction (RD). Postictal generalized EEG suppression (PGES) may follow generalized tonic-clonic seizures (GTCS). Following GTCS patients have impaired arousal and may be motionless. Patients with SUDEP are usually prone. Postictal immobility (PI) may contribute to SUDEP by not permitting repositioning of the head to allow unimpeded ventilation. To determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
93
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 24 publications
(81 reference statements)
6
93
0
1
Order By: Relevance
“…In a review of 9 published studies comprising 542 patients, it was shown that the percentage of focal seizures during REM sleep is extremely low, being around 1%. 22 Of note, similar to our findings, 13 Alexandre and colleagues 15 found a correlation between the occurrence of PGES, but not PGES duration, for any patient or seizure variables studied, and PGES occurrence was significantly increased when GTCS occurred in sleep. However, total seizure duration was shorter and no difference in the duration of the tonic phase was observed in seizures starting in sleep compared to those starting during wakefulness.…”
Section: Epilepsia Ilaesupporting
confidence: 88%
See 3 more Smart Citations
“…In a review of 9 published studies comprising 542 patients, it was shown that the percentage of focal seizures during REM sleep is extremely low, being around 1%. 22 Of note, similar to our findings, 13 Alexandre and colleagues 15 found a correlation between the occurrence of PGES, but not PGES duration, for any patient or seizure variables studied, and PGES occurrence was significantly increased when GTCS occurred in sleep. However, total seizure duration was shorter and no difference in the duration of the tonic phase was observed in seizures starting in sleep compared to those starting during wakefulness.…”
Section: Epilepsia Ilaesupporting
confidence: 88%
“…13 Although PGES occurs more frequently in sleep, the duration of PGES is not influenced by the state of the patient. 13 Although PGES occurs more frequently in sleep, the duration of PGES is not influenced by the state of the patient.…”
Section: Epilepsia Ilaementioning
confidence: 99%
See 2 more Smart Citations
“…Postictal immobility, presumed to reflect depressed arousal and/or motor function 19,20 , is commonly observed after FBTCS and has been associated with postictal EEG attenuation in scalp recordings. Interestingly, the timing of postictal immobility with respect to IPA was highly variable.…”
Section: Discussionmentioning
confidence: 99%